2021
DOI: 10.47144/phj.v54i2.2090
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation Observed on 48 Hours Holter Monitoring in Patients With Sinus Rhythm on Electrocardiogram

Abstract: Objectives: To find out the prevalence of undiagnosed atrial fibrillation and the risk factors associated with atrial fibrillation in patients with complaints of palpitations having normal sinus rhythm on electrocardiogram. Methodology: The descriptive cross-sectional study was carried out from 1st of January 2017 to 31st of December 2020 at Department of Cardiology, Chaudhary Pervaiz Elahi Institute of Cardiology, Multan. All the patients presented with the complaints of palpitations for six months with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…AF is difficult to detect because of its paroxysmal nature and the fact that it is frequently asymptomatic. Raza et al calculated the rate of AF development at the age of 40-75 years as 24% 19 . In our study, the mean age was found 60.9±13.5 years and the rate of AF development was calculated as 36% between the ages of 40-75 years.…”
Section: Discussionmentioning
confidence: 99%
“…AF is difficult to detect because of its paroxysmal nature and the fact that it is frequently asymptomatic. Raza et al calculated the rate of AF development at the age of 40-75 years as 24% 19 . In our study, the mean age was found 60.9±13.5 years and the rate of AF development was calculated as 36% between the ages of 40-75 years.…”
Section: Discussionmentioning
confidence: 99%